Lightweight high-strength Mg-Li-Al-Mn alloy and preparation method thereof
By controlling the content of Li, Al and Mn and the preparation process, a stable MgLiAl2+Al8Mn5 reinforced phase is formed, which solves the problems of strength and mechanical properties stability of Mg-Li alloy, and achieves both lightweight, high strength and stable mechanical properties.
Patent Information
- Application Number
- CN202411694859.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing Mg-Li alloys are difficult to maintain low density and stable mechanical properties while improving their strength, especially instability in long-term mechanical properties.
By controlling the addition amount of Li, combined with the addition of a small amount of Al and trace Mn, a stable combination of MgLiAl2+Al8Mn5 enhanced phase is formed, which inhibits the formation of metastable reinforced phase and softened phase, and improves grain refinement of the alloy through extrusion molding and heat treatment.
The low density and high strength of Mg-Li-Al-Mn alloy are achieved, while the mechanical properties stability of the alloy is improved, the yield strength and tensile strength are significantly improved, and the elongation and density are also within a reasonable range.
Smart Images

Figure CN119506672A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal materials, and in particular relates to a light and high-strength Mg-Li-Al-Mn alloy and a preparation method thereof. Background Art
[0002] Mg-Li alloy is the lightest structural metal material with the advantages of low density, high specific strength and specific stiffness. It has broad application prospects in aerospace, national defense, transportation and electronic products. Adding Li to magnesium can not only reduce the density, but also cause changes in the magnesium lattice structure, thereby reducing the c / a value from the original 1.642 to 1.607, resulting in a decrease in the interplanar spacing of the basal plane {0001}, and an increase in the symmetry of the magnesium alloy lattice, which activates the non-basal plane {10-10}〈11-20〉 slip system and improves its plasticity. When the lithium content in magnesium reaches 5.7-10.3wt%, the alloy is composed of a mixture of α-Mg solid solution of a close-packed hexagonal lattice and β-Li solid solution of a body-centered cubic lattice. Although β-Li can greatly improve the deformation ability of the Mg-Li alloy, the strength of the alloy is low. Adding a small amount of Al to Mg-Li alloy can significantly improve the strength of the alloy, but its tensile strength is difficult to exceed 300MPa, and the metastable strengthening phase MgAlLi2 formed in the alloy will decompose into the softening phase AlLi at 50-70°C, resulting in unstable long-term mechanical properties of Mg-Li alloy. Therefore, it is of great significance to develop lightweight, high-strength and stable mechanical properties Mg-Li alloy. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the main purpose of the present invention is to provide a light and high-strength Mg-Li-Al-Mn alloy, which improves its plasticity by controlling the amount of Li added; at the same time, by adding a small amount of Al and a trace amount of Mn, it can break the conventional trend that the beneficial MgLiAl2 phase in the alloy is easy to precipitate when the Al content is high, and can form a unique stable MgLiAl2+Al8Mn5 strengthening phase combination in the alloy, and inhibit the formation of the metastable strengthening phase MgAlLi2 and the softening phase AlLi. At the same time, the MgLiAl2+Al8Mn5 particles have a significant grain refining effect on the dynamic recrystallization of the magnesium alloy during the extrusion process, and can significantly improve the strength of the alloy. By controlling the content ratio of each element and the preparation process, it is ensured that the Mg-Li-Al-Mn alloy has low density and stable mechanical properties, solving the problem that the Mg-Li alloy is difficult to have both light weight and high strength.
[0004] The object of the present invention is to provide a method for preparing the lightweight and high-strength Mg-Li-Al-Mn alloy.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A light and high-strength Mg-Li-Al-Mn alloy comprises the following components by weight percentage: Li: 3.0-9.0%, Al: 0.5-4.0%, Mn: 0.2-1.5%, and the rest is magnesium and unavoidable impurities, and the total impurity content is less than or equal to 0.3%.
[0007] Preferably, the lightweight and high-strength Mg-Li-Al-Mn alloy comprises the following components in weight percentage: Li: 3.84%, Al: 3.07%, Mn: 0.29%, and the rest is magnesium and unavoidable impurities, and the total impurity content is less than or equal to 0.3%.
[0008] Preferably, the lightweight and high-strength Mg-Li-Al-Mn alloy comprises the following components in weight percentage: Li: 4.17%, Al: 3.357%, Mn: 0.51%, and the rest is magnesium and unavoidable impurities, and the total impurity content is less than or equal to 0.3%.
[0009] Preferably, the lightweight and high-strength Mg-Li-Al-Mn alloy comprises the following components in weight percentage: Li: 8.11%, Al: 0.99%, Mn: 1.26%, and the rest is magnesium and unavoidable impurities, and the total impurity content is less than or equal to 0.3%.
[0010] In certain specific embodiments, the lightweight and high-strength Mg-Li-Al-Mn alloy contains MgLiAl2 phase and Al8Mn5 phase.
[0011] The present invention also provides a method for preparing the aforementioned lightweight and high-strength Mg-Li-Al-Mn alloy, comprising the following steps:
[0012] A) pure Mg ingot, pure Al ingot, Mg-3Mn master alloy and pure Li ingot are mixed according to the formula requirements, and smelted to obtain an alloy melt;
[0013] B) casting the alloy melt obtained in step A) to obtain an ingot;
[0014] C) heat treating and extruding the ingot in step B) to obtain a light and high-strength Mg-Li-Al-Mn alloy.
[0015] In certain specific embodiments, step A) is specifically as follows: placing a stainless steel crucible containing a pure Mg ingot into a melting furnace, raising the furnace temperature to 720°C in a vacuum melting furnace and keeping it warm for 10 minutes; then adding a Mg-3Mn master alloy and a pure Al ingot and keeping it warm for 20 minutes; lowering the temperature to 680°C, adding a pure lithium ingot into the crucible and keeping it warm for 10 minutes to prepare an alloy melt.
[0016] In some specific embodiments, the process further includes preheating and drying the pure Mg ingot, the pure Al ingot and the Mg-3Mn master alloy before smelting at 180-250° C. for 3-4 hours.
[0017] In some specific embodiments, step B) is specifically as follows: taking out a stainless steel crucible with a diameter of Φ80-100 mm from the smelting furnace, putting it into cold water, quenching it, and after cooling, taking out the ingot and turning it to obtain an ingot with a diameter of Φ70-90 mm.
[0018] In some specific embodiments, the step C) is specifically as follows: after removing the oxide scale or contamination layer on the surface of the ingot obtained in step B), placing it in a heating furnace for heat treatment, then extruding the heat-treated ingot in an extruder, and air-cooling it to room temperature to obtain a lightweight and high-strength Mg-Li-Al-Mn alloy.
[0019] Furthermore, the heat treatment temperature is 240-260°C, and the time is 3.5-4.5 hours; the extrusion molding conditions are: extrusion ratio is 22-26:1, extrusion speed is 1.5-2.5mm / min, and extrusion temperature is 260°C-300°C.
[0020] Compared with the prior art, the present invention has at least the following advantages:
[0021] 1. Compared with the traditional Mg-Li-Al alloy, the lightweight and high-strength Mg-Li-Al-Mn alloy provided in the present application can segregate at the front edge of the α-Mg phase solidification interface by adding a specific content of Mn, inhibit the growth of primary dendrites, refine and spheroidize the α-Mg phase grains, and improve the strength of the alloy.
[0022] 2. The lightweight and high-strength Mg-Li-Al-Mn alloy of the present invention introduces a specific content of Al and Mn elements to break the conventional trend that the beneficial MgLiAl2 phase is easy to precipitate in the alloy when the Al content is high, and can form a unique stable MgLiAl2+Al8Mn5 strengthening phase combination in the alloy, and inhibit the formation of the metastable strengthening phase MgAlLi2 and the softening phase AlLi. The stable MgLiAl2 and Al8Mn5 second phase particles can be dispersedly distributed after extrusion. The second phase pins the grain boundary and hinders the movement of dislocations, which can bring significant strengthening effects to the magnesium alloy.
[0023] 3. The lightweight and high-strength Mg-Li-Al-Mn alloy provided by the present invention forms a stable MgLiAl2+Al8Mn5 phase which can inhibit grain growth during plastic deformation of the alloy and improve the strength and plasticity of the alloy by refining the grains.
[0024] 4. The lightweight and high-strength Mg-Li-Al-Mn alloy provided by the present invention has a yield strength of 166-248 MPa, a tensile strength of 199-331 MPa, an elongation of 11.3-16.1%, and a density of 1.526-1.632 g / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0026] Figure 1 This is a graph showing the XRD test results of the lightweight and high-strength Mg-Li-Al-Mn alloy in Example 1 of the present invention;
[0027] Figure 2 is a metallographic diagram of the lightweight and high-strength Mg-Li-Al-Mn alloy in Example 1 of the present invention;
[0028] Figure 3 This is a SEM image of the lightweight and high-strength Mg-Li-Al-Mn alloy in Example 1 of the present invention;
[0029] Figure 4 : is the stress-strain diagram of the lightweight and high-strength Mg-Li-Al-Mn alloy in Example 1 of the present invention;
[0030] Figure 5 is a metallographic diagram of the lightweight and high-strength Mg-Li-Al-Mn alloy in Example 3 of the present invention;
[0031] Figure 6 This is a SEM image of the lightweight and high-strength Mg-Li-Al-Mn alloy in Example 3 of the present invention;
[0032] Figure 7 1 is the stress-strain diagram of the lightweight and high-strength Mg-Li-Al-Mn alloy in Example 3 of the present invention. DETAILED DESCRIPTION
[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0034] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0035] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0036] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0037] In the following embodiments, the pure Mg ingots, pure Al ingots, Mg-3Mn (wt.%) intermediate alloys and pure Li used are commercially available products, wherein the purity of the pure Mg ingots is ≥99.9%, the purity of the pure Al ingots is ≥99.5%, the purity of the pure Li ingots is ≥99.9%, and the purity of the Mg-3Mn intermediate alloy ingots is ≥99.5%.
[0038] The model of the tensile machine used in the test method used in the following embodiments is UTM4104, the model of the metallographic microscope used is OLYMPUS PMG3; and the model of the scanning electron microscope used is FEI NOVA 400.
[0039] Example 1
[0040] The lightweight and high-strength Mg-Li-Al-Mn alloy of this embodiment is composed of the following components in mass percentage: Li: 3.84%, Al: 3.07%, Mn: 0.29%, and the rest is magnesium and unavoidable impurities.
[0041] The method for preparing the lightweight and high-strength Mg-Li-Al-Mn alloy of this embodiment comprises the following steps:
[0042] (1) Preheating: pure Mg ingot, pure Al ingot, Mg-3Mn master alloy and pure Li ingot are prepared according to the above mass fractions, and the raw materials pure Mg ingot, pure Al ingot and Mg-3Mn master alloy are preheated and dried at 250° C. for 4 h;
[0043] (2) Melting: The preheated alloy obtained in step (1) is placed in a stainless steel crucible, and then the crucible containing the pure Mg ingot is placed in a melting furnace. In a vacuum melting furnace, the furnace temperature is raised to 720°C and kept warm for 10 min; then the Mg-3Mn master alloy and the pure Al ingot are added and kept warm for 20 min; the temperature is lowered to 680°C, and the pure Li ingot is added to the crucible and kept warm for 10 min to prepare an alloy melt;
[0044] (3) Casting: removing the scum on the surface of the alloy melt obtained in step (2), letting it stand for 5 minutes, taking out a stainless steel crucible with a diameter of 90 mm, putting it into cold water for water quenching, taking out the ingot and turning it to obtain an alloy ingot with a diameter of 80 mm;
[0045] (4) homogenization annealing: after removing the oxide scale or contamination layer on the surface of the alloy ingot obtained in step (3), the alloy ingot is wrapped with aluminum foil and placed in a furnace for homogenization annealing. The homogenization annealing temperature is 250° C., the heat preservation time is 4 h, and the ingot is cooled with the furnace;
[0046] (5) Extrusion: The alloy ingot after homogenization annealing in step (4) is placed in an extrusion barrel for extrusion deformation. The extrusion rate of the extrusion deformation is 2 mm / s, the extrusion temperature is 300° C., and the extrusion ratio is 25:1, so as to obtain a cylindrical extruded rod with a final size of φ16 mm, that is, a lightweight and high-strength Mg-Li-Al-Mn alloy.
[0047] In this embodiment, the mechanical properties of the magnesium-lithium alloy prepared by the extrusion process are tested. The yield strength of the extruded Mg-Li-Al-Mn alloy is 248 MPa, the tensile strength is 331 MPa, the elongation is 16.1%, and the density is 1.632 g / cm 3 ;
[0048] The XRD test results of the magnesium-lithium alloy rod prepared in this embodiment are as follows: Figure 1 As shown, the metallographic structure is Figure 2 As shown in the SEM images Figure 3 The stress-strain curve is shown in Figure 4 As shown in the figure, the second phase of the Mg-3.84Li-3.07Al-0.29Mn alloy is mainly LiMgAl2 phase and Al8Mn5 phase. The matrix structure and the black second phase of the alloy are elongated along the extrusion direction, and the crushed second phase particles are dispersed on the matrix, which is conducive to recrystallization nucleation and hindering dislocation movement during hot extrusion. The refined second phase, substructure, and grains make the alloy have good strength and plasticity.
[0049] Example 2
[0050] The lightweight and high-strength Mg-Li-Al-Mn alloy of this embodiment is composed of the following components in mass percentage: Li: 4.17%, Al: 3.35%, Mn: 0.51%, and the rest is magnesium and unavoidable impurities.
[0051] The preparation method of the lightweight high-strength Mg-Li-Al-Mn alloy in this embodiment is the same as the preparation method in Example 1. The yield strength of the prepared lightweight high-strength Mg-Li-Al-Mn alloy is 239 MPa, the tensile strength is 278 MPa, the elongation is 12.9%, and the density is 1.610 g / cm 3 .
[0052] Example 3
[0053] The lightweight and high-strength Mg-Li-Al-Mn alloy of this embodiment is composed of the following components in mass percentage: Li: 8.11%, Al: 0.99%, Mn: 1.26%, and the rest is magnesium and unavoidable impurities.
[0054] The difference between the preparation method of the light and high-strength Mg-Li-Al-Mn alloy in this embodiment and the preparation method in Example 1 is that the extrusion temperature of the alloy is 260°C, the yield strength is 166MPa, the tensile strength is 199MPa, the elongation is 11.3%, and the density is 1.526g / cm 3 Mg-Li-Al-Mn alloy.
[0055] The metallographic structure of the magnesium-lithium alloy rod prepared in this embodiment is as follows: Figure 5 As shown in the SEM images Figure 6 The stress-strain curve is shown in Figure 7 As shown in the figure, the Mg-8.11Li-0.99Al-1.26Mn alloy is composed of matrix α-Mg+β-Li and some black second phase particles, and the second phase particles are evenly distributed on the phase boundary of the alloy.
[0056] Comparative Example 1
[0057] This comparative example relates to a lightweight magnesium-lithium alloy. The composition of the alloy is substantially the same as that of Example 1, except that the alloy does not contain the Mn element. The preparation method of the magnesium alloy is the same as that of Example 1.
[0058] The density of the lightweight magnesium alloy prepared in this comparative example is 1.621 g / cm 3 The room temperature mechanical properties are: yield strength 253MPa, tensile strength 247MPa, elongation: 16.8%.
[0059] Since the magnesium-lithium alloy does not contain the Mn element, the grain refining effect of the cast alloy is insufficient. Secondly, the Al8Mn5 strengthening phase cannot be formed in the alloy, resulting in low alloy strength.
[0060] Comparative Example 2
[0061] This comparative example relates to a lightweight magnesium-lithium alloy, the composition of which is substantially the same as that of Example 3, except that it does not contain the Al element. The preparation method of the magnesium alloy is the same as that of Example 3.
[0062] The density of the lightweight magnesium alloy prepared in this comparative example is 1.507 g / cm 3 The room temperature mechanical properties are: yield strength 111MPa, tensile strength 156MPa, and elongation 19.2%.
[0063] Since the magnesium-lithium alloy does not contain Al, it fails to form MgLiAl2 and Al8Mn5 strengthening phases, resulting in low alloy strength. In addition, the alloy is composed of a mixture of α-Mg solid solution with a close-packed hexagonal lattice and β-Li solid solution with a body-centered cubic lattice. Although β-Li can greatly improve the deformation ability of the Mg-Li alloy, the strength of the alloy is low.
[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A lightweight and high-strength Mg-Li-Al-Mn alloy, characterized in that: The invention comprises the following components in weight percentage: Li: 3.0-9.0%, Al: 0.5-4.0%, Mn: 0.2-1.5%, and the rest is magnesium and unavoidable impurities, and the total content of the impurities is less than or equal to 0.3%.
2. The lightweight and high-strength Mg-Li-Al-Mn alloy according to claim 1, characterized in that: The composition includes the following components by weight percentage: Li: 3.84%, Al: 3.07%, Mn: 0.29%, and the rest is magnesium and unavoidable impurities, and the total content of the impurities is less than or equal to 0.3%.
3. The lightweight and high-strength Mg-Li-Al-Mn alloy according to claim 2, characterized in that: The light and high-strength Mg-Li-Al-Mn alloy contains MgLiAl2 phase and Al8Mn5 phase.
4. A method for preparing a lightweight and high-strength Mg-Li-Al-Mn alloy according to any one of claims 1 to 3, characterized in that: The steps include: A) pure Mg ingot, pure Al ingot, Mg-3Mn master alloy and pure Li ingot are mixed according to the formula requirements, and smelted to obtain an alloy melt; B) casting the alloy melt obtained in step A) to obtain an ingot; C) heat treating and extruding the ingot in step B) to obtain a light and high-strength Mg-Li-Al-Mn alloy.
5. The method for preparing a lightweight and high-strength Mg-Li-Al-Mn alloy according to claim 4, characterized in that: Step A) is specifically as follows: placing a stainless steel crucible containing a pure Mg ingot into a melting furnace, raising the furnace temperature to 720° C. in a vacuum melting furnace and keeping the temperature for 10 min; then adding a Mg-3Mn master alloy and a pure Al ingot and keeping the temperature for 20 min; lowering the temperature to 680° C., adding a pure lithium ingot into the crucible and keeping the temperature for 10 min to prepare an alloy melt.
6. The method for preparing a light and high-strength Mg-Li-Al-Mn alloy according to claim 5, characterized in that: The method also includes preheating and drying the pure Mg ingot, the pure Al ingot and the Mg-3Mn intermediate alloy before smelting at 180-250° C. for 3-4 hours.
7. The method for preparing a light and high-strength Mg-Li-Al-Mn alloy according to claim 6, characterized in that: Step B) is specifically as follows: taking out a stainless steel crucible with a diameter of Φ80-100 mm from the smelting furnace, putting it into cold water for water quenching, and after cooling, taking out the ingot and turning it to obtain an ingot with a diameter of Φ70-90 mm.
8. The method for preparing a light and high-strength Mg-Li-Al-Mn alloy according to claim 7, characterized in that: The step C) specifically comprises: removing the oxide scale or contamination layer on the surface of the ingot obtained in step B), placing it in a heating furnace for heat treatment, and then extruding the heat-treated ingot in an extruder, and air-cooling it to room temperature to obtain a lightweight and high-strength Mg-Li-Al-Mn alloy.
9. The method for preparing a light and high-strength Mg-Li-Al-Mn alloy according to claim 8, characterized in that: The heat treatment temperature is 240-260°C, and the time is 3.5-4.5 hours; the extrusion molding conditions are: extrusion ratio is 22-26:1, extrusion speed is 1.5-2.5mm / min, and extrusion temperature is 260°C-300°C.